(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article delves into the importance of syntactic analysis in educating students on the grammatical structures of verbs. It examines how syntactic scrutiny assists instructors in proficiently conveying understanding of verb formations to learners. Through an exhaustive examination of pertinent literature and an empirical investigation, this study underscores the function of syntactic analysis in augmenting language pedagogy.